Technology Adoption and Pedagogical Shifts in Central Sulawesi's Secondary Education - Satria Ahmar, Dewi; Azzajjad, Muhammad Fath (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
This research looks at the adoption patterns of educational technology in Palu City, Sigi Regency, and Donggala Regency, three areas in Central Sulawesi.  Although there are notable differences between urban and rural settings, the quick incorporation of technology in education is essential to enhancing learning results.  This study's main goal is to examine how secondary schools in these areas have used instructional technology from Education 1.0 to Education 5.0.  Using a quantitative descriptive approach, the study gathers survey data from senior high school students attending Islamic, public, and private institutions as well as vocational schools.  With 160 student responses, the analysis is arranged according to five major regions: Palu City, Sigi Regency, and Donggala Regency, according to the results, Sigi Regency exhibits a moderate adoption of Education 2.0 and early Education 3.0 tools, whereas Palu City exhibits the highest degree of technological integration, especially in Education 3.0 and 4.0.  The biggest obstacles, however, are found in Donggala Regency, where most schools continue to use Education 1.0 and 2.0 approaches.  The report identifies the primary obstacles, such as regional differences in digital resources, poor infrastructure, and insufficient teacher preparation.  Considering the findings, it is evident that in order to close the digital gap and guarantee the successful integration of educational technology in all areas, a more equal allocation of resources and focused legislative initiatives are necessary.